An in situ exploration of subsurface defect migration to a liquid water‐exposed rutile TiO2(110) surface by XPS. (16th November 2020) - Ahmed, M. H. Mesbah; Temperton, Robert H.; O'Shea, James N.
Abstract : The ability of titanium dioixide to split water into OH − and H + species is heavily dependent on the behaviour of defects in the crystal structure at or near the surface. We present an in situ study of defect migration in rutile TiO2 (110) conducted using X‐ray photoelectron spectroscopy (XPS). First, surface and subsurface defects were created in the crystal by argon ion sputtering. Subsequent in situ exposure of the defective crystal to liquid water healed the surface defects, whereas the subsurface remained defective. The sample was then annealed while XPS was used to monitor the concentration of titanium defects. At low annealing temperatures, Ti 3+ was observed to migrate from the subsurface to the surface. Further annealing gradually restored the surface and subsurface to the defect‐free Ti 4+ form, during which the changes in abundance of Ti 1+, Ti 2+ and Ti 3+ defects are discussed.